2019
DOI: 10.3389/fnbeh.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

Monoamines, Insulin and the Roles They Play in Associative Learning in Pond Snails

Abstract: Molluscan gastropods have long been used for studying the cellular and molecular mechanisms underlying learning and memory. One such gastropod, the pond snail Lymnaea stagnalis , exhibits long-term memory (LTM) following both classical and operant conditioning. Using Lymnaea , we have successfully elucidated cellular mechanisms of learning and memory utilizing an aversive classical conditioning procedure, conditioned taste aversion (CTA). Here, we present the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 156 publications
(205 reference statements)
0
19
0
Order By: Relevance
“…The tracks of experimental snails are also obviously shorter since the speed of locomotion was lower in ketanserin-treated animals. Totani et al, 2019). Recently, immediate effects of intense locomotion on decision-making under uncertainty were reported in the snail Lymnaea stagnalis, suggesting a possible link between motor and cognitive functions of serotonin in mollusks (D'yakonova, 2014;Korshunova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracks of experimental snails are also obviously shorter since the speed of locomotion was lower in ketanserin-treated animals. Totani et al, 2019). Recently, immediate effects of intense locomotion on decision-making under uncertainty were reported in the snail Lymnaea stagnalis, suggesting a possible link between motor and cognitive functions of serotonin in mollusks (D'yakonova, 2014;Korshunova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin activates many forms of behavior (Sakharov, 1990;Gillette, 2006) and participates in the regulation of cognitive functions, such as learning and memory, in mollusks (Balaban et al, 2016;Nikitin et al, 2018;Totani et al, 2019). The neurons that control locomotion in L. stagnalis include a large serotonergic PeA cluster of cells which release serotonin to the muscles and cilia in the sole (Syed and Winlow, 1989;Longley and Peterman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…That is, while the shell is undergoing the majority of its repair, the snail continues to experience stress and should have heightened defensive behaviours. Thirdly, insulin has been shown to enhance LTM formation in L. stagnalis (Murakami et al, 2013a,b;Hatakeyama et al, 2013;Mita et al, 2014;Totani et al, 2019). It is known that molluscan insulin-related peptides (MIPs) are synthesized by about 150 neurons (the light green cells) in the cerebral ganglia of L. stagnalis and these are released both centrally in the CNS and in the periphery to regulate shell growth (Geraerts, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, injecting glucose into 5-day fooddeprived snails does not alter the impaired learning and memory (Mita et al 2014a(Mita et al , 2014b. On the basis of these complicated results, we concluded that insulin plays a critical role in CTA formation and consolidation (Totani et al 2019).…”
Section: Conditioned Taste Aversion In Lymnaeamentioning
confidence: 83%